1987
DOI: 10.1002/sdr.4260030103
|View full text |Cite
|
Sign up to set email alerts
|

A system dynamics model for estimating heroin imports into the United States

Abstract: A small system dynamics model of the heroin supply in the United States has proved useful in estimating heroin imports and anticipating effects of changes in imports. This paper describes the structure of the model and its application to import data over a ten‐year period. Of particular interest is the way in which the model has been used to flag inconsistencies and fill gaps in federal data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Much of the literature suggested that price and availability of supply should be central to any analysis of illicit drug markets. Supporting this economic approach was an existing system dynamics model of the national heroin market (Gardiner and Shreckengost 1987), which was already familiar to the NIJ and other government agencies, was small and easy to understand, and had proved able to reproduce some key heroin indicator time series data.…”
Section: Cocaine Prevalence Modelmentioning
confidence: 99%
“…Much of the literature suggested that price and availability of supply should be central to any analysis of illicit drug markets. Supporting this economic approach was an existing system dynamics model of the national heroin market (Gardiner and Shreckengost 1987), which was already familiar to the NIJ and other government agencies, was small and easy to understand, and had proved able to reproduce some key heroin indicator time series data.…”
Section: Cocaine Prevalence Modelmentioning
confidence: 99%
“…SD scholars have also developed several applications that enable people to understand and improve the actions embedded in complex systems. In fact, more than 57 percent of the 100 most cited articles in SDR between 1985 and 2017 are related to the modeling of dynamic problems of wide interest, such as global warming (Naill et al, ; Sterman and Sweeney, ), sustainable development (Harich, ; Moxnes, ), drug use dynamics (Gardiner and Shreckengost, ; Homer, ; Coyle and Alexander, ), conservation policies (Ford and Bull, ), water scarcity (Fernandez and Selma, ) and disasters (Cooke, ; Owens et al, ). The third most cited paper in SDR was written by Forrester () (Cit: 180; ACit: 7.5), and it relates to both of the described streams in SDR: (i) formal procedures and (ii) the modeling and analysis of complex dynamic problems.…”
Section: Overview Of Sd Articles Published Between 1985 and 2017mentioning
confidence: 99%
“…We refer the interested reader to additional resources and a more thorough discussion of SD tools [6,8,12]. SD tools have been increasingly applied to a wide range of public health problems, such as diabetes [13,14], tobacco [15], substance use [16][17][18], HIV/AIDS [19][20][21][22], and obesity [23,24], to help understand the complexities driving these problems and elucidate potential policy approaches. The purpose of this systematic review was to identify, summarize, and reflect on SD applications in the injury prevention literature and highlight future opportunities for SD to contribute to injury prevention research and practice.…”
Section: Introductionmentioning
confidence: 99%